Hemichorea as a presentation of acute rheumatic fever: a case report - Zafar, Khwaja Saifullah; Singh, P.S.; Wafai, N. A. (International Journal of Research in Medical Sciences, 2017)
Chorea is a major manifestation of acute RF and is the only evidence of RF in approximately 20% of cases. We report on a 15-year-old boy who presented with transient right side involuntary jerky movements, apical systolic murmur, sinus bradycardia, arthralgia, elevated antistreptolysin O titer and ESR, who was diagnosed with acute rheumatic fever and improved with haloperidol, prednisolone, digoxin, aspirin and furosemide and was given benzathine penicillin prophylaxis for future RF. Patient is faring well in follow up visits. We present our case because of its rarity.